Application of the Snowball Throwing Learning Model on the Topic of Drawing Closer to Allah SWT through Asmaul Husna - Iffah Firzanah; Anita Puji Astutik (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Application of the Snowball Throwing Learning Model on the Topic of Drawing Closer to Allah SWT through Asmaul HusnaObjective: This study aims to describe the process of applying the Snowball Throwing learning model to the material “Close to Allah SWT through Asmaul Husna” and to examine its strengths and weaknesses. Method: This study uses a descriptive-qualitative method. Data collection was conducted through observation, interviews, and documentation, with analysis carried out through data reduction, presentation of results, and drawing of conclusions. Results: The Snowball Throwing learning model enhances student participation, understanding, and learning outcomes, while also fostering a sense of responsibility, cooperation, and mutual respect. Challenges such as time constraints and method adjustments can be overcome with effective classroom management and teacher guidance. Conclusion: The Snowball Throwing learning model can increase student engagement and understanding of Asmaul Husna, as well as strengthen positive social interactions. Contribution: This study contributes to the development of more engaging and interactive learning methods in Islamic Education, providing insights into the use of the Snowball Throwing model as an innovative approach to improve cognitive and social outcomes in the classroom. INDONESIAN: Penerapan Model Pembelajaran Snowball Throwing pada Materi Dekat dengan Allah SWT melalui Asmaul HusnaTujuan: Penelitian ini bertujuan untuk menggambarkan proses penerapan model pembelajaran Snowball Throwing pada materi